A Legal Review of The Granting of Abolition and Amnesty in The Cases of Tom Lembong and Hasto Kristiyanto Under Indonesian Criminal Law - Muhammad Havez; Muhammad Rusjana; Erine Nur Maulidya (Journal of Law and Policy Transformation, 2025)
This study aims to analyze the legal basis and mechanism for granting abolition to Tom Lembong and amnesty to Hasto from the perspective of Indonesian criminal law. Furthermore, this study also discusses the legal implications of these abolitions and amnesties for law enforcement and legal certainty in Indonesia. The research method used is a normative legal approach, examining laws and regulations, doctrine, and relevant literature. The analysis shows that granting abolition and amnesty is a presidential prerogative, as stipulated in the constitution and laws. However, its implementation must adhere to the principles of justice, legal certainty, and expediency. The granting of abolition to Tom Lembong and amnesty to Hasto has sparked legal debate, particularly regarding the limits of executive authority over the criminal justice process. These legal implications include the potential to reduce the deterrent effect, create a political precedent in law enforcement, and demand stricter regulations to ensure that abolition and amnesty policies do not conflict with the principles of the rule of law.